AL-QUR’AN MENJAWAB TANTANGAN HAK ASASI MANUSIA - Munif Mahadi Attamimi; Muhammad Hariyadi (LP2M Universitas PTIQ Jakarta, 2020)
The conclusion of this study explains the nature of human dignity inherent in it from birth and its chronological process. The Al-Qur'an explains in detail and sequentially that the glorification of human dignity occurs in several phases. The first is before his existence on earth (unseen world): when Allah wants to make a human caliph (ruler) on earth, he orders the angels to prostrate to Adam as a respect, excellence, exaltation and knowledge are taught as a whole. Second, when in the womb where the fetus is well cared for and is well cared for by getting nutritious food through the placenta. Third, when he is in the world, he is given a perfect body shape, makes it easy for him to control the land and sea, is given the right to manage the world and everything in it, is given good sustenance, and is honored by other creations of Allah SWT. Fourth, be glorified at the time of death, at funerals, and after death. To maintain and protect the dignity of human beings, Allah has prepared three important components for humans as a basis for protecting human rights (HAM), namely faith, law, and morals. The method used in interpretation related to this research is the thematic method or maudui 'which is combined with qualitative methods as a basis for library research, Al-Qur'an verses, hadith syarif, journals, articles, seminars, and conference proceedings.